Pembangunan Aplikasi Mobile Kehadiran Guru Berbasis Geofence, Firebase ID, dan Face Capture Pada SMAN 1 Ulakan Tapakis - Muhammad Zaim Milzam; Jefril Rahmadoni; Afriyanti Dwi Kartika (Jurnal Nasional Teknologi dan Sistem Informasi, 2026)
The teacher attendance process at SMAN 1 Ulakan Tapakis is still carried out manually using paper forms, which are prone to input errors, data loss, and manipulation practices such as leaving absences behind. Efforts to implement technology in the form of fingerprint devices were made, but did not function continuously due to technical constraints. This condition causes the attendance data recapitulation and reporting process to be inefficient and take a long time. Based on these problems, this study aims to build a mobile teacher attendance application based on geofence, Firebase ID, and face capture as a solution to improve data integrity and efficiency in the attendance process at SMAN 1 Ulakan Tapakis. This system was developed using the Waterfall method, through the stages of needs analysis, system design, implementation, and testing. The results of functional testing show that all application features run according to design and can validate teacher attendance automatically based on the location and identity of the user. In addition, the results of efficiency testing show that this system can significantly save time in the attendance and reporting process compared to manual methods. Thus, this application is considered effective in improving the integrity of attendance data and the efficiency of the teacher attendance administration process at SMAN 1 Ulakan Tapakis.